Integrated Transcriptomic and Proteomic Analyses Reveal the Role of NprR in Bacillus anthracis Extracellular Protease Expression Regulation and Oxidative Stress Responses - Wang, Yanchun; Jiang, Na; Wang, Bowen; Tao, Haoxia; Zhang, Xin; Guan, Qing; Liu, Chunjie (Frontiers in Microbiology, 2020)
NprR is a protein of Bacillus anthracis that exhibits moonlighting functions as either a phosphatase or a neutral protease regulator that belongs to the RNPP family. We previously observed that the extracellular protease activity of an nprR deletion mutant significantly decreased within in vitro cultures. To identify the genes within the regulatory network of nprR that contribute to its protease activity, integrated transcriptomic and proteomic analyses were conducted here by comparing the nprR deletion mutant and parent strains. A total of 366 differentially expressed genes (DEGs) between the strains were observed via RNA-seq analysis. In addition, label-free LC-MS/MS analysis revealed 503 differentially expressed proteins (DEPs) within the intracellular protein fraction and 213 extracellular DEPs with significant expressional differences between the strains. The majority of DEGs and DEPs were involved in environmental information processing and metabolism. Integrated transcriptomic and proteomic analyses indicated that oxidation-reduction-related GO terms for intracellular DEPs and endopeptidase-related GO terms for extracellular DEPs were signiﬁcantly enriched in the mutant strain. Notably, many genes involved in protease activity were largely downregulated in the nprR deletion mutant cultures. Moreover, western blot analysis revealed that the major extracellular neutral protease Npr599 was barely expressed in the nprR deletion mutant strain. The mutant also exhibited impaired degradation of protective antigen, which is a major B. anthracis toxin component, thereby resulting in higher protein yields. Concomitantly, another global transcriptional regulator, SpxA1, was also dramatically downregulated in the nprR deletion mutant, resulting in higher sensitivity to oxidative and disulfide stress. These data consequently indicate that NprR is a transcriptional regulator that controls genes whose products function as extracellular proteases and also is involved in oxidative stress responses. This study thus contributes to a more comprehensive understanding of the biological function of NprR, and especially in the middle growth stages of B. anthracis.